Pemanfaatan Akun Instagram @lost.in.jogja sebagai Media Promosi Wisata Cycling Tour di Yogyakarta - Aqilah Farah Rizki Ramadhan; Anggun Anindya Sekarningrum (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the use of the Instagram account @lost.in.jogja as a promotional medium for cycling tour tourism in Yogyakarta within the context of experience-based tourism marketing. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. Data analysis is conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, and is interpreted through the AISAS framework (Attention, Interest, Search, Action, Share) to map audience behavior in responding to digital promotional content. The findings indicate that Instagram is utilized in an integrated manner using aesthetic visual content, experience-based storytelling, and the optimization of platform features such as Reels, Stories, Highlights, and Direct messages. Visual content plays a role in attracting audience attention, while storytelling builds emotional engagement and interest. Instagram features facilitate information search and interaction, which encourage service usage decisions, while user experiences are redistributed through user-generated content that expands promotional reach organically. These findings confirm that Instagram functions as a communication ecosystem that integrates content, interaction, and user experience in supporting the effectiveness of experience-based tourism promotion.